EDUCATION IN HIGHER SCHOOL: FORMATION OF ADMINISTRATIVE COMPETENCE OF FUTURE TEACHERS - REBUKHA, Liliia; ZVARYCH, Ganna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Annotation. The article characterizes the professional and pedagogical competence of a specialist, which includes instrumental (knowledge of the profession, abilities, skills, educational and professional activities, independent decision-making) and individual-personal (various types of actions, which involve observing pedagogical tact, sociability, benevolence, emotional balance, parity in relationships) components. Administrative competence has been updated. For its analysis, functional-analytical and technological approaches were chosen with the description of admministrative functions, within which the essential characteristics are described. We included goal-setting, anticipation in planning, forecasting of future results and skillful reflection of management activities as components of managerial competence. We associate administrative competence with the acquired managerial abilities and certain practical technological skills of a specialist for effective performance of professional functions. The implementation of motivational-targeted, prognostic, informational-communicational, organizational-research and regulatory-corrective functions in pedagogical activity is described, based on the management competence formed in the future teacher, which includes the acquisition of certain knowledge, abilities and skills in the management of an educational institution. A study was conducted to identify the formed administrative competencies of future teachers in the management of educational institutions and their readiness for future managerial activities in an educational institution. The obtained results showed that the majority of masters have developed a high level of "personnel-oriented" behavior, which is characterized by providing full freedom of action to subordinates and self-development and professional growth and completion of the tasks set by them; a high indicator of "task-oriented" behavior, which allows the future head of an educational institution to encourage teachers to work, to support their work capacity and professional competence, to carefully plan the work of the team and the educational institution as a whole. It is concluded that the master's degree in the educational program "Management of Educational Institutions" has the formation of managerial knowledge, abilities, skills, abilities, professionally significant personality qualities, which serve as the main signs of a teacher's administrative competence.